Pengaruh Need For Uniqueness dan Bandwagon Effect terhadap Purchase Intention Melalui Value-Expressive Function Of Attitude Sebagai Variabel Intervening: Studi Empiris pada Hijab Buttonscarves - Meydiawati, Meydiawati; Pebrianti, Wenny; Afifah, Nur; Listiana, Erna (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This research aims to test and analyze the influence of need for uniqueness and bandwagon effect on purchase intention through the value-expressive function of attitude as an intervening variable. Sampling uses purposive sampling, which is a type of non-probability sampling in which the sampling technique uses certain considerations. The number of samples in this study was 150 respondents. The data analysis technique in this research uses a Structural Equation Model (SEM) approach based on Partial Least Square (PLS). The research results show that the need for uniqueness and the bandwagon effect have a significant effect on the value-expressive function of attitude. Need for uniqueness and bandwagon effect have a significant influence on purchase intention. Value-expressive function of attitude has a significant effect on purchase intention. Value-expressive function of attitude mediates the indirect influence of need for uniqueness and bandwagon effect on purchase intention. All hypothesis testing results show a strong level of significance and reliability. The implication of these findings is the importance of Buttonscarves in designing a marketing strategy that not only emphasizes product exclusivity, but is also able to exploit consumers' desires to express their personal values through the products they buy